Acquired reactive perforating collagenosis and pseudoporphyric bullous dermatosis in a hemodialysis patient. Issue 3 (2nd February 2016) - Sabanis, Nikos; Paschou, Eleni; Gavriilaki, Eleni; Kalaitzoglou, Asterios; Papanikolaou, Dimitrios; Vasileiou, Sotiris; Amplianitis, Ioannis
Abstract: Hemodialysis patients present with a broad spectrum of specific and nonspecific skin disorders, which rarely coexist. We report an exceptional case of a hemodialysis patient that developed acquired reactive perforating collagenosis and pseudoporphyric bullous dermatosis on the basis of common skin disorders which include hyperpigmentation, pruritus, xerosis cutis, and Linsday's nails. Interestingly, our patient presented with two unusual but distinctive cutaneous dermopathies on the background of other commonly seen skin alterations. The patient was successfully treated with allopurinol and N‐acetylcysteine. Avoidance of potentially triggering factors such as alcohol, sunlight exposure and certain medication was recommended. Thus, increasing clinical awareness, assiduous investigation and early treatment of skin disorders are required to improve the prognosis and quality of life in this patient population.